An integral approach to environmental restoration in the face of climate change, cultural identity, and archaeological heritage: the case of Tzintzuntzan, Michoacán, México - Lindig Cisneros, Roberto (2023)
[Introduction]: Conservation and restoration of the ecological and cultural heritage is a necessity given the current environmental crisis, in particular when considering the effects of climate change. This can be achieved through interdisciplinary research that allows the creation of strategies for restoring complex biocultural landscapes. [Objective]: To propose strategies for ecocentric, biocultural and productive ecological restoration in Tzintzuntzan (place of hummningbirds) a landscape dominated by precolumbian archaeological remains in the riverbanks of lake Paztcuaro, México, considering the expected effects of climate change. [Metodology]: A GIS was created with information about gthe socioenvironmental conditions of the study site, a climate change model was also elaborated for year 2050 and the loss of water lake water level was estimated. [Resultados]: From the present conditions of the vegetation, climatic modelling and the presence of archaeological remains we obtained that for the year 2050 most of the area (89%) of forests dominated by oaks and pines will have a climate appropriate for dry tropical vegetation. Considering the distribution of archaeological remains and the urban area we propose ecocentric, biocultural and production restoration strategies. [Conclusions]: A biocultural approach to restoration is desirable because it allows the recovery of ecological and cultural elements of the socioecosystem, with a emphasis in adaptation to climate change and the recovery of hummingbird habitat, being the hummingbirds the most important link between nature and culture in the region.